2010
DOI: 10.1021/ol1003127
|View full text |Cite
|
Sign up to set email alerts
|

“Click” Synthesis of Nonsymmetrical Bis(1,2,3-triazoles)

Abstract: Unsymmetrically 1,1'-disubstituted 4,4'-bis-1H-1,2,3-triazoles 4 have been prepared from 4-ethynyl-1,2,3-triazoles 5 and azides. Following a "double-click" strategy, two complementary approaches were implemented for the preparation of the key 4-ethynyltriazole intermediates 5: (a) the stepwise Swern oxidation/Ohira-Bestman alkynylation of readily available 4-hydroxymethyl-1,2,3-triazoles 8 and (b) the stepwise cycloaddition of TMS-1,4-butadiyne 9. The method is highlighted by its compatibility with orthogonall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(27 citation statements)
references
References 30 publications
2
24
1
Order By: Relevance
“…This 32CA reaction is presents a very low regioselectivity, as TS-m1 is only 0.34 kcal mol−1 lower in energy than , indicating that this 32CA reaction is only under kinetic control. These results are in disagreement with the meta regioselectivity observed experimentally [8].…”
Section: Kinetic Study Of the 13-dipolar Cycloaddition Reaction Of Tcontrasting
confidence: 67%
See 1 more Smart Citation
“…This 32CA reaction is presents a very low regioselectivity, as TS-m1 is only 0.34 kcal mol−1 lower in energy than , indicating that this 32CA reaction is only under kinetic control. These results are in disagreement with the meta regioselectivity observed experimentally [8].…”
Section: Kinetic Study Of the 13-dipolar Cycloaddition Reaction Of Tcontrasting
confidence: 67%
“…It was recently reported that is possible to impart some regioselectivity into these thermal cycloadditions by utilizing sterically or catalyze or electronically biased alkynes [6,7]. Herein, we used new theory recently proposed by Domingo named a Molecular Electron Density Theory (MEDT) to study the cycloaddition reaction of the Prop-2-yn-1-ol with azides 1, 2 and 3 experimentally studied by Jesus MA et al [8] (Scheme 1). Our aim is to explain the regioselectivity experimentally found.…”
mentioning
confidence: 99%
“…The formation of the triazole products was monitored by HPLC and mass spectrometry using selected ion recording (SIR) detection (LC/MS-SIR) after 24 h at 25°C. After analysis of each reaction mixture, only azide 8 42) was sufficiently accelerated in its cycloaddition with alkyne 4a in the presence of the hDAO enzymes to yield a detectable amount of triazole 9 (at this point not distinguished as to whether a syn-and/or anti-substituted triazole) in the background with great reproducibility by LC/ MS-SIR measurement (Fig. 3).…”
Section: Resultsmentioning
confidence: 99%
“…Due to overlap with other bands the analysis of the triazole band at 1400-1500 cm − 1 [ 28 ] was impossible, allowing only a quantifi cation of the amount of the azide band during the reaction. As seen in Figure 1 a, the azide band (red arrow) decreases continuously with time until complete disappearance, thus allowing the determination of azideconversion during the reaction progress.…”
Section: 35-tris(prop-2-ynyloxymethyl)benzene (5)mentioning
confidence: 99%